Bureaucratic Reform Resistance in Indonesia - Muhammad Hasyem; Ferizaldi Ferizaldi; Syamsuddin Syamsuddin; Tarmidi Tarmidi (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
Formulating, rearranging, and improving and perfecting bureaucratic behavior to become better, productive, professional, efficient, and effective for the formation of a pattern, mode, system and better governance. Commitment, good etiquette, seriousness, and hard work from all parties are absolute, and must be upheld. Our country's political leadership is very weak, there is a politicization of the bureaucracy, there is resistance (resistance) from the bureaucrats themselves and the competence of implementing bureaucratic reform. Political commitment needs to be emphasized and formulated into a solid policy, guide and guide in its implementation along with an evaluation of all activities and there must be an institution that is responsible for making and overseeing the bureaucratic reform policy. Focus, priorities and targets for achievement need to be set. Systematic, consistent, accurate, and controlled from an agenda that is carried out can avoid stagnation, saturation, and can also be separated from the image of mere pretense where every regime in power in the beginning always has a breakthrough or image.Penelitian ini membahas mengenai upaya pemerintah dalam merumuskan, menata kembali, dan meningkatkan serta menyempurnakan perilaku birokrasi menjadi lebih baik, produktif, profesional, efisien, dan efektif untuk pembentukan pola, modus, sistem, dan tata kelola yang lebih baik. Komitmen, etika yang baik, keseriusan, dan kerja keras dari semua pihak adalah mutlak, dan harus dijunjung tinggi. Kepemimpinan politik negara kita sangat lemah, ada politisasi birokrasi, ada resistensi (perlawanan) dari birokrat itu sendiri dan kompetensi pelaksana reformasi birokrasi. Komitmen politik perlu ditegaskan dan dirumuskan menjadi suatu kebijakan, pedoman dan pedoman yang kokoh dalam pelaksanaannya disertai evaluasi terhadap seluruh kegiatan dan harus ada lembaga yang bertanggung jawab membuat dan mengawasi kebijakan reformasi birokrasi. Fokus, prioritas dan target pencapaian perlu ditetapkan. Sistematis, konsisten, akurat, dan terkontrol dari sebuah agenda yang dijalankan dapat menghindari stagnasi, kejenuhan, dan juga dapat dipisahkan dari citra kepura-puraan belaka dimana setiap rezim yang berkuasa pada awalnya selalu memiliki terobosan atau citra.